Rapid Intervention of Chlorpromazine and Promethazine for Hibernation-Like Effect in Stroke: Rationale, Design, and Protocol for a Prospective Randomized Controlled Trial - Lv, Shuyu; Zhao, Wenbo; Rajah, Gary B.; Dandu, Chaitu; Cai, Lipeng; Cheng, Zhe; Duan, Honglian; Dai, Qingqing; Geng, Xiaokun; Ding, Yuchuan (Frontiers in Neurology, 2021)
Background: Following an acute ischemic stroke (AIS), rapidly initiated reperfusion therapies [i.e. intravenous thrombolysis (IVT) and endovascular treatment (EVT)] demonstrate robust clinical efficacy. However, only a subset of these patients can benefit from these therapies due to their short treatment windows and potential complications. In addition, many patients despite successful reperfusion still have unfavorable outcomes. Thus, neuroprotection strategies are urgently needed for AIS patients. Chlorpromazine and promethazine (C+P) have been employed in clinical practice for antipsychotic and sedative purposes. A clinical study has also shown a neuroprotective effect of C+P on patients with cerebral hemorrhage and subarachnoid hemorrhage. The safety, feasibility, and preliminary efficacy of intravenous administration of C+P in AIS patients within 24 hours of onset will be elucidated. Methods: A prospective randomized controlled trial is proposed with AIS patients. Participants will be randomly allocated to an intervention group and a control group with a 1:1 ratio (n = 30) and will be treated with standard therapies according to the current stroke guidelines. Participants allocated to the intervention group will receive intravenous administration of C+P (chlorpromazine 50 mg and promethazine 50 mg) within 24 hours of symptom onset. The primary outcome is safety (mainly hypotension), while the secondary outcomes include changes in functional outcome and infarction volume. Discussions: This study on Rapid Intervention of Chlorpromazine and Promethazine for Hibernation-like Effect in Stroke (RICHES) will be the first prospective randomized controlled trial to ascertain the safety, feasibility, and preliminary efficacy of intravenous C+P as a neuroprotection strategy in AIS patients. These results will provide parameters for future studies, provide insights into treatment effects, and neuroprotection with phenothiazine in AIS. Key words: acute ischemic stroke (AIS), phenothiazine, neuroprotection, intravenous thrombolysis, rt-PA Trial Registration: www.chictr.org.cn, identifier: ChiCTR2000038727